Electronic Receipt of Document Control System using Technology Acceptance Model - Frieyadie Frieyadie; Faisal Muharam (STMIK Budi Darma, 2023)
AbstractThe document control system in a company is the company's effort to provide a means to find information and documents related to the company. Implementing a manual system for the documentation system (still in the form of physical paper stored in document shelves/cabinets) takes a long time in the work process, making it difficult for the employee in charge to control the document. The variables used in this study are the ease of use and effectiveness using the Technology Acceptance Model (TAM) method. In collecting the data, the researchers made observations, interviews, literature studies, and questionnaires. Of the 273 population of employees using the document control system, a sample of 73 correspondents was taken based on the formula. Sampling using a simple random sampling technique. The data analysis method used is quantitative analysis with multiple linear regression analysis. In calculating the data, researchers used the SPSS data processing application version 27. Based on the results of the study, it was found that 13.5% of employees accepted the existence of electronic document control technology based on the ease and effectiveness of the electronic document control system. The results of the three hypotheses tested found that two hypotheses were accepted and 1 hypothesis was rejected.